Repercussions of Teleworking During the Covid-19 Pandemic in the Educational Field. Case of the Technical University of Machala - Montealegre-Ramón, Génesis Nayeli (2022)
The present work is oriented to carry out an analysis through a survey aimed at knowing and exploring the repercussions of teleworking in times of the Covid-19 Pandemic in the educational field, specifically for the case of teachers of the Faculty of Business Sciences of the Technical University of Machala. That is, to determine the challenges and problems they faced in the implementation of the teleworking modality as a result of the government's declaration of social distancing due to the possible contagion of the Covid-19 virus in 2020. The research work was carried out with an approach descriptive-exploratory, considering the responses to the survey sent online to teachers of the Faculty of Business Sciences of the Technical University of Machala. The results obtained point to an increase in working hours and work overload, teachers say they feel physically and mentally tired, many of them have presented ailments and discomfort due to the constant time they spend sitting in front of their computers, the survey also showed a imbalance between the time allocated for work and the development of personal and family obligations. This is due to the excess of teaching work days.